Fatal interplay between acquired thrombotic thrombocytopenic purpura and posterior reversible encephalopathy syndrome: a case report - Prajakta Kakde, MBBS; Amol Andhele, MD; Abhinav Kadam, MD; Gautam Bedi, MBBS; Sourya Acharya, MD; Sunil Kumar, MD (Radiology Case Reports)
Acquired thrombotic thrombocytopenic purpura (TTP) is a rare haematological emergency characterised by severe ADAMTS13 deficiency, leading to thrombotic microangiopathy and multiorgan dysfunction. Posterior reversible encephalopathy syndrome (PRES) is a neurological disorder associated with endothelial dysfunction, often secondary to uncontrolled hypertension or autoimmune conditions. We present a case of a 22-year-old male who presented with vomiting, headache, and right upper limb weakness, followed by a hypertensive crisis and generalised seizures. Initial investigations revealed severe thrombocytopenia, microangiopathic hemolytic anaemia, and acute kidney injury, raising suspicion for thrombotic microangiopathy. MRI findings confirmed PRES, while the presence of schistocytes and markedly reduced ADAMTS13 activity led to the diagnosis of acquired TTP. The patient was treated with plasma exchange, immunosuppressive therapy, corticosteroids, and antihypertensive agents. Despite aggressive management, the disease progressed to multiorgan failure, and the patient succumbed to the illness. This case highlights the fatal interplay between TTP and PRES, emphasising the need for early recognition and timely intervention. The coexistence of these 2 rare conditions presents a diagnostic and therapeutic challenge, underscoring the importance of prompt plasma exchange and immunosuppressive therapy in such critically ill patients.